1981
DOI: 10.1086/296130
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the "Tax Effects" of Inflation Under Historical Cost Accounting Methods

Abstract: It is often argued that the failure to use indexation (i.e., the use of historical cost accounting methods) implies that real income tax rates will vary directly with rates of inflation. This substantive effect of mere bookkeeping methods is often predicted even though it is recognized to have some adverse implications. This is the "tax effects of inflation" hypothesis. The major objective of this paper is to examine the descriptive adequacy of this hypothesis using a variety of macro-economic data for the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 20 publications
0
14
2
2
Order By: Relevance
“…The Theory Following Fisher, suppose that the real and monetary sectors of the economy are causally independent. Two other explanations, which have less support in the literature, are (i) that the U.S. tax system, via, for example, its treatment of depreciation, leads to high inflation having a negative impact on equities (see Feldstein (1980), Gonedes (1981), and Hasbrouck (1983) for examples of this literature), and (ii) that there is either irrationality on the part of agents or general market inefficiency (e.g., Modigliani and Cohn (1979) and Summers (1983)), such as confusion between nominal and real rates. This can lead to a causal relation between stock returns and inflation, through the correlation between stock returns and both corporate and personal income.…”
Section: Stock Returns and Expected Inflation: A Theoretical Explmentioning
confidence: 99%
“…The Theory Following Fisher, suppose that the real and monetary sectors of the economy are causally independent. Two other explanations, which have less support in the literature, are (i) that the U.S. tax system, via, for example, its treatment of depreciation, leads to high inflation having a negative impact on equities (see Feldstein (1980), Gonedes (1981), and Hasbrouck (1983) for examples of this literature), and (ii) that there is either irrationality on the part of agents or general market inefficiency (e.g., Modigliani and Cohn (1979) and Summers (1983)), such as confusion between nominal and real rates. This can lead to a causal relation between stock returns and inflation, through the correlation between stock returns and both corporate and personal income.…”
Section: Stock Returns and Expected Inflation: A Theoretical Explmentioning
confidence: 99%
“…He demonstrated that a once-and-for-all increase in general price level leads to a 'tax shield' loss on the depreciation charges, and hence to a reduction in the real cash flow of companies. Subsequently, and, more recently, Hong (1977) and Gonedes (1981) confirmed the validity of this effect. The depreciation effect represents a wealth reallocation from the private sector to the public sector.…”
Section: Corporate Sectormentioning
confidence: 83%
“…(5), which makes it easier to interpret the coefficients and economic significance for FIFO and LIFO variables. Gonedes (1981) also estimates the association between the real corporate tax burden and inflation and fails to find the positive association between these items that is predicted by the tax hypothesis. There are, however, noticeable differences between his empirical approach and ours, which we discuss here to demonstrate the research design choices that we make relative to choices that are made when using more aggregated data.…”
Section: Data and Research Designmentioning
confidence: 90%
“…For example, Anderson et al (1983), Matolcsy (1984), and Ferris and Makhija (1988) find evidence supporting the tax hypothesis; Gonedes (1981), Geske and Roll (1983), Kaul (1987), and Lee (2010) do not find support; and Bernard and Hayn (1986) find mixed evidence. Also, French et al (1983), Bernard (1986), and Pearce and Roley (1988) indirectly examine the tax hypothesis using stock returns around inflation announcements.…”
Section: Introductionmentioning
confidence: 99%